Penerapan Konsep Techno-Nature pada Perancangan Interior Lobby dan Fasilitas Pendukung Area Rawat Jalan Winthrop International Hospital di Surabaya - S.P. Honggowidjaja, Ivan Djiemesha (Intra, 2014)
This design would make a hospitalâs lobby interior that not only provide health services, but also make patients feel comfortable by giving some facilities. Facilities to be added to the hospitalâs lobby are interior design and furnitures ambience, the furnitures are made to facilitate the disabled as well, smart hospital system, as well as a good circulation system for the smooth operation of the lobby. The addition of a better atmosphere at the hospital can provide an increement of hope in patientâs healing process. In addition, the smart hospital system and a good circulation system can support the activities that occur in the hospitalâs lobby.